Eksplorasi Kritis Hermeneutika Fazlur Rahman dalam Interpretasi Ayat Riba - Muhammad Nizhamuddin (Kuras Institute, 2025)
Fazlur Rahman’s hermeneutics, particularly his double movement theory, offers a novel approach to understanding Islamic texts, including Qur’anic verses on riba (usury). This approach emphasizes two key stages: first, examining the socio-historical context of the verses at the time of revelation, and second, applying the universal values of these verses in a contemporary setting. Through this method, Rahman seeks to bridge the gap between normative texts (das Sollen) and modern socio-economic realities (das Sein), ensuring that Islamic law remains relevant to changing times. However, his approach has not been without criticism, particularly from traditional scholars who argue that Rahman’s reinterpretation of riba contradicts classical Islamic jurisprudence, which categorically prohibits bank interest. This study evaluates Rahman’s hermeneutics in interpreting riba verses by integrating a historical-critical analysis with contemporary exegetical studies. The findings indicate that while Rahman’s approach provides an alternative perspective on Islamic legal interpretation, careful application of hermeneutical methods is necessary to maintain the fundamental principles of Islamic law